2017
DOI: 10.1111/iep.12253
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and oestrogen receptors as potential prognostic markers for patients with ductal carcinoma in situ treated with surgery and radiotherapy

Abstract: Ductal carcinoma in situ (DCIS) is a heterogeneous disease that has been investigated less extensively than invasive breast cancer. Women with DCIS are mainly treated with conservative surgery almost exclusively followed by radiotherapy. However, as radiation treatment is not always effective, the search for biomarkers capable of identifying DCIS lesions that could progress to invasive cancer is ongoing. Although conventional biomarkers have been thoroughly studied in invasive tumours, little is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A retrospective analysis of 42 Ductal Carcinoma in situ of the breast (DCIS) patients treated with surgery followed by radiotherapy showed that AR expression was considerably higher in relapsed tumors (p = 0.0005), whereas ERα was higher in non-relapsed ones. The AR:ERα ratio was different among the subgroups (p = 0.0033), indicating the unfavorable prognostic role of AR and AR/ERα in this subset of patients [21]. Consistently, another study revealed that the AR:ERα value could be used as a highly specific and sensitive prognostic tool for in situ relapse or progression to invasive subtypes [22].…”
Section: Prognostic Value Of Ar By Different Breast Cancer Subtypesmentioning
confidence: 65%
“…A retrospective analysis of 42 Ductal Carcinoma in situ of the breast (DCIS) patients treated with surgery followed by radiotherapy showed that AR expression was considerably higher in relapsed tumors (p = 0.0005), whereas ERα was higher in non-relapsed ones. The AR:ERα ratio was different among the subgroups (p = 0.0033), indicating the unfavorable prognostic role of AR and AR/ERα in this subset of patients [21]. Consistently, another study revealed that the AR:ERα value could be used as a highly specific and sensitive prognostic tool for in situ relapse or progression to invasive subtypes [22].…”
Section: Prognostic Value Of Ar By Different Breast Cancer Subtypesmentioning
confidence: 65%
“…Other studies showed that AR expression level was higher in DCIS adjacent to IDC compared to pure DCIS [20,21]. In statistical analyses of the expression of several biomarkers of breast cancer, AR did not show statistical signi cance as a risk factor for recurrence [22].Recently, based on the concept of competition between AR and ER, Ravaioli et al suggested AR/ER ratio as a prognostic marker for DCIS [23]. AR indeed was associated with a favorable prognosis in this study population which correlates with the previously reported biological effect of AR as an ER signal inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated an unfavorable prognostic role of the AR/ER ratio in different subsets of patients (i.e., patients with ductal carcinoma in situ of the breast), independently of treatment ( i.e. , surgery alone or surgery plus radiotherapy) [1214]. Similarly, Rangel et al and Cochrane et al reported a poorer prognosis when the AR/ER ratio was higher in the primary tumor of early BC patients [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Given that we aimed to calculate the AR/ER and AR/PgR ratios, AR expression value was considered as a continuous variable (percentage of immunopositive tumor cells ranging 0-100%) and not dichotomous (positive/negative). As reported in our previous work, when ER or PgR were negative, the AR value was used instead of AR/ER and AR/PgR values [12].…”
Section: Methodsmentioning
confidence: 99%